Nghiên cứu chuyển hóa 3-oxominovin thành ancaloit minovin - Châu, Phan Đình (Vietnam Journal of Chemistry, 2014)
Minovine (1), an alkaloid of Vinca minor, was prepared by transformation of 3-oxominovine (3) is threes steps: The first the compound 3 was reacted with P2O5 into 3-thioxo-minovine (4), methylattion of that gave the salt 5 and in the end this product was reduced with NaBH4 to form minovine (1).